HUBUNGAN MINAT BACA DENGAN KETERAMPILAN MENULIS NARASI EKSPOSITORIS SISWA KELAS VII SMP NEGERI 11 PADANG - Martavia, Ria Fianti; Thahar, Harris Effendi; Asri, Yasnur (Universitas Negeri Padang, 2016)
ABSTRACTÂ This article is written to discuss the results of research on the relationship of interest in reading the narrative expository writing skills of students of class VII SMP Negeri 11 Padang. This research data in the form of a score questionnaire interest in reading and writing skills test score results expository narrative. The data was obtained through two types of tests, namely questionnaire to measure the level of mastery of reading and performance test to measure the level of mastery of narrative expository writing skills. This research is a quantitative experimental method. The results of this research are three: (1) the level of interest in reading students' mastery of grade VII SMP Negeri 11 Padang are in qualification More than Enough (LDC) with an average value of 74.49, (2) the level of mastery of narrative expository writing skills graders VII SMP Negeri 11 Padang are in qualification More than Enough (LDC) with an average value of 74.55, and (3) based on the t-test, the alternative hypothesis (H1) is accepted at 95% significance level and degrees of freedom (df) = n-1 because thitung> ttable (31.40> 1.68).Â Kata kunci : hubungan, minat baca, narasi ekspositoris